Pure Gold or Therapeutic Alloy?: Some Issues Raised By The Conference "Change: Psychoanalytic Perspectives" - Ivey, Gavin (PINS-Psychology in Society, 2026)
Change was the fitting theme for the first international psychoanalytic conference in Africa, held in Cape Town over the first weekend in April 1998. Whatever the expectations of the international guests, nothing prepared them for the ambivalent welcome and three days of drama to which the natives subjected them. Despite the genteel surroundings of the four-star Arthur's Seat hotel, this long-awaited conference was no sedate affair. After the second day's proceedings the collective tension had reached such a pitch that the organising committee was compelled to arrange an extraordinary group therapy session for the delegates. The urbane British group analyst, Malcolm Pines, contained the group's palpable aggression with a masterful intervention disguised as an introduction. With an airy wave of his hand, looking more like an orchestra conductor than the man in the middle of a hostile psychoanalytic horde, Dr Pines announced, "Let the blood flow"! The informal group therapy managed to diffuse some of the tension, but delegates spent the remainder of the conference trying to understand the underlying dynamics behind the emotionally charged conference atmosphere.